A noção de competência enquanto princípio de organização curricular - Thais Almeida Costa (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
The main aim of this paper is toanalyse the current ascension of thenotion of competence and its influenceon curricular reform in elementaryeducation. It seeks to understand howcurricula are being structured andformulated on the basis of the notion ofcompetence and how this is beingassimilated into teaching discourse. Tothis end, it discusses a case studycarried out in the night school classesof the municipal school network ofBetim, which recently elaborated acurriculum by competencies, currentlybeing implemented in local schools.The notion of competence was taken asthe principle point of reference for theofficial curriculum proposal as well asfor the discourse of some teachers withregard to the incorporation of theproposal into the daily life of theschool. The results of the study suggestthat the notion of competence is takenas the principle element for curricularorganisation, and assumes animportant role with regard to thecontents to be taught. However, due toits plastic and polysemic nature, thenotion is not understood by theteachers who end up by relating it tothe most diverse concepts.